Using Pathway-Specific Comprehensive Exposure Scores in Epidemiology: Application to Oxidative Balance in a Pooled Case-Control Study of Incident, Sporadic Colorectal Adenomas - Dash, Chiranjeev (Oxford University Press, 2013)
Identifying associations of risk factors sharing the same pathway with disease risk is complicated by small individual effects and intercorrelated components; this can be addressed by creating comprehensive exposure scores. We developed and validated 3 novel weighting methods (literature review–derived, study data–based, and a Bayesian method that combines prior knowledge with study data) to incorporate components into a pathway score for oxidative balance in addition to a commonly used method that assumes all components contribute equally to the score. We illustrate our method using pooled data from 3 US case-control studies of sporadic colorectal adenoma (1991–2002). We created 4 oxidative balance scores (OBS) to reflect combined summary measures of dietary and nondietary antioxidant and prooxidant exposures. A higher score represents a predominance of antioxidant exposures over prooxidant exposures. In the pooled data, the odds ratios comparing the highest tertile of OBS with the lowest for adenoma risk ranged from 0.38 to 0.54 for the 4 measures; all were statistically significant. These findings suggest that 1) OBS are indicators of oxidative balance and may be inversely associated with colorectal adenoma risk and 2) using comprehensive exposure scores may be preferable to investigating individual component-disease associations for complex exposures, such as oxidative balance.